The effect of drought on gas exchange and water potential in leaves of seven Mediterranean woody species - Gucci, R; Massai, R; Casano, S; Gravano, E; Lucchesini, M (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The water relations and gas exchange parameters of Arbutus unedo, Cistus monspeliensis, Erica arborea, Myrtus communis, Phillyrea latifolia, Pistacia lentiscus, and Quercus ilex growing in the shrubland vegetation at the Parco Naturale della Maremma (Italy), were studied over two consecutive years. At high leaf water potentials, photosynthetic rates and stomatal conductance were relatively low in all species but C. monspeliensis. Stomatal conductance remained relatively high in C. monspeliensis leaves as soil moisture was depleted, whereas A. unedo, E. arborea, M. communis, and P. lentiscus were more conservative in water use. P. latifolia and Q. ilex showed a drought-tolerant behaviour.
Keywords: Drought tolerance; leaf water potential; Phenology; Stomatal conductance

Morpho-anatomical aterations in leaves of Fagus sylvatica L. and Quercus ilex L. in different environmental stress condition - Grossoni, P; Bussotti, F; Tani, C; Gravano, E (Chemosphere, 1998)
By means of anatomical and foliar structure observations, this paper examines the ecological behaviour of two different species of broadleaf (a mesophile one, beech, and a xerophile one, holm-oak), under different conditions of water supply. The purpose of this study was to evaluate their response in relation to possible climate changes. The results highlight certain similarities of behaviour (reduction of leaf surface, increased leaf thickness, increase of mechanical structures in xeric stands). The main difference between the two species lies in the tannins content, which increase in the epidermal cells (vacuoles and walls) only in beech trees in xeric conditions
Keywords: Fagus sylvatica; foliar structure; Quercus ilex; xeric conditions (voyant)